Tempeh Nugget Innovation: Creative Steps Towards Empowered Students - Warti'ah Warti'ah; Ahmad Afghor Fahruddin; Risma Ayu Kinanti; Asni Atammin Nisa; Elmania Galuh Freellylah; Alfa Syifaiyah (TAAWUN, 2025)
The community service is carried out by a team of community service that aims to empower the students of the Mamba'ul Hisan Sidayu Gresik Islamic Boarding School through tempeh nugget management assistance activities. The methods used in the guided training are carried out offline and online through YouTube media. 12 students attended the training. Starting from preparation in November to training activities in December. The tempeh nugget-making training held at the Mamba'ul Hisan Islamic Boarding School had a significant positive impact on the participants, especially the students. The results of the evaluation showed that 82% of the participants managed to understand the material presented, and 85% were able to apply practical skills well. Through this training, students not only gain new knowledge but are also able to produce innovative products in the form of tempeh nuggets. This product is an added value in the processing of tempeh ingredients, as well as opening opportunities for students to develop independent businesses. The success of this training shows the effectiveness of the empowerment of the students so that they become more empowered individuals and ready to contribute to the economic empowerment of the pesantren and the community.